Jordan Economic Monitor, Spring 2021 : Uncertain and Long Trail Ahead - World Bank (World Bank, Washington, DC, 2021)
Despite recent progress on vaccine developments to combat the COVID-19 (coronavirus) pandemic, the global economic recovery remains surrounded by high uncertainty. During the first half of 2020, global economic output declined by an unprecedented level, resulting in a sharp fall in global trade. The latest estimates from the IMF WEO in April 2021 indicate that the global economy contracted by 3.3 percent in 2020. This contraction is substantially deeper than one observed during the Global Financial Crisis of 2007 - 08. However, recent trends are pointing toward a strong recovery for global economic activity in the second half of 2021 supported by substantial fiscal and monetary stimuli. Nevertheless, the extent of the protraction is closely linked to vaccine rollout, which is gaining critical mass in some developed economies, but remains uneven across the world. Indeed, the World Bank is projecting global economy to grow by 4 percent in 2021. Nevertheless, this global outlook retains an important country-specific component which depends on the adjustment capacity of each economy as well as the effectiveness of its policy to minimize permanent scarring to the economy as well as pace and scale of domestic vaccine rollout.